Papaya Leaf (Carica papaya L.) Active Fraction Effective as Bioinsectiside Against Anopheles species (Diptera: Culicidae) Larva Invitro Study - Chairil Anwar; Febriyanto Febriyanto; Dalilah Dalilah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2018)
ABSTRACT Malaria is one of the spread-disease that become a global public health problem included Indonesia. One of the controlling approach of vector-borne disease is by avoiding direct contact of human and mosquitoes. Natural insecticide is an alternative method that can be used. Carica papaya L. is one of the natural insecticide because contains of alkaloid, flavonoid and saponin. This research was aimed to determine the activity of active fraction. was a quasi-experiment research with post test only group design. This research was conducted in April – June 2017. Extraction and fractination was performed in laboratory of MIPA Biologi of Sriwijaya University. The experiment was performed in laboratory of Entomologi Baturaja. The sample of the research was Anopheles sp. larva instar III and IV. Larvacide test used 6 different concentrations which was 0,125%, 0,25%, 0,5%, 1,0% and 2,0% with aquadest as a control. Anova test and post hoc analysis with SPSS 22 software. The result of efficacy test to Anopheles sp. larva showed that N-hexan was the fraction with highest larvacide ability that kill 95% larva at 2% concentration level. Thin layer chromatography test showed a compound of Terpenoid. Activity test of active fraction N-heksan of papaya leaf with the highest mortality rate 92,5% and the lowest 46,25%. LC50 fraction N-heksan of papaya leaf was high toxicity at 24 hours of observation. Anova test showed there was significant influence and difference of various concentration of active fraction of papaya leaf to the mortality of Anopheles sp. larva with p value < α (0,00<0,05). Key words : Anopheles sp. larva, N-hexan fraction of papaya leaf, larvacide